Penerapan Model Pembelajaran Problem Based Learning dengan Memanfaatkan Potensi Lokal untuk Meningkatkan Aspek Problem Solving pada Higher-Order Thinking Skills - Dhora Vasminingtya; Sajidan Sajidan; Umi Fatmawati (Universitas Sebelas Maret, 2014)
This research’s aim is to increase the problem solving skill of the students in X-A of SMA Negeri Sragen Billingual Boarding School Gemolong academic Year 2013/2014. The matter is about Enviroment Pollution through Problem Based Learning application by using local area potention. This research is a class action research which consists of three cycles. Each cycle contains of planning, implementing, observing and reflecting. The research subject is the students in X-A of SMA Negeri Sragen Billingual Boarding School Gemolong academic Year 2013/2014. Data of research were obtained by test and non test technique. Data validation were used triangulation of methods and triangulation of observers. The obtained data were analyzed using descriptive technique.The results of this research showed that according triangulation the average percentage for IDEAL problem solver. IDEAL problem solver design measured with performance assement consist of IDEAL process and IDEAL product. The average of IDEAL problem solver become value of problem solving skill for every student. The result of the research shows that the implementation of problem based learning increase the students’ problem solving skill that covers the IDEAL problem solver. The total average of IDEAL problem solver in the X-A class SBBS increased from 42,0 move up into 85,7 score. This research’s conclusion is the implementation of problem based learning can increase the problem solving skill of the students in of SMA Negeri Sragen Billingual Boarding School Gemolong academic Year 2013/2014 about enviroment pollution material. Key Words: Problem based learning, problem solving skill